2011
DOI: 10.1111/j.1439-0507.2011.02089.x
|View full text |Cite
|
Sign up to set email alerts
|

Substituted 2‐aminothiophenes: antifungal activities and effect on Microsporum gypseum protein profile

Abstract: The increasing recognition and importance of fungal infections, the difficulties encountered in their treatment and the increase in resistance to antifungal agents have stimulated the search for therapeutic alternatives. The objective of this study was to evaluate the antifungal activities of three substituted 2-aminothiophenes (1, 2 and 3) against some fungal species. The synthesis of substituted 2-aminothiophenes was carried out through the most versatile synthetic method developed by Gewald et al. The antif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…The DPPH free radical scavenging activity of compound 6 was comparable to that of the standard antioxidant vitamin C. These results corroborate the FRAP assay, where this compound exhibited the best antioxidant activity. Previous study has shown strong antioxidant activity of azo compounds performed by using DPPH free radical scavenging assay and metal chelating method [40]. The results of the antioxidant study show that these azo compounds may have great relevance in the prevention and therapies of diseases in which oxidants or free radicals are implicated [40].…”
Section: Resultsmentioning
confidence: 99%
“…The DPPH free radical scavenging activity of compound 6 was comparable to that of the standard antioxidant vitamin C. These results corroborate the FRAP assay, where this compound exhibited the best antioxidant activity. Previous study has shown strong antioxidant activity of azo compounds performed by using DPPH free radical scavenging assay and metal chelating method [40]. The results of the antioxidant study show that these azo compounds may have great relevance in the prevention and therapies of diseases in which oxidants or free radicals are implicated [40].…”
Section: Resultsmentioning
confidence: 99%
“…The interesting results that we recently found from the antifungal activities and the effects on Microsporum gypseum protein profile [13] of these compounds stimulated us to carry out similar investigations on azo compounds derived from them. In the present work, we report on the synthesis and the structural elucidation of five new thienylazothiophene derivatives 3-7 obtained from substrates 1.…”
Section: Introductionmentioning
confidence: 93%
“…EI mass spectra (70 eV) were measured on a LCQ Classic spectrometer from Thermo Fisher Scientific Company. 1 H NMR spectra (750 MHz) and 13 C NMR spectra (187.5 MHz) were recorded in DMSO-d 6 on a Bruker AV III instrument. All reagents were purchased from Aldrich and Fluka and were used without further purification.…”
Section: Experimental Generalmentioning
confidence: 99%
“…Absorbance was read at 530 nm for yeasts or at 600 nm for bacteria and adjusted with the saline solution to match that of a 0. to give a final concentration of 10 6 yeast cells/mL and 10 6 CFU/mL for bacteria (Wayne, 1992;Fogue et al, 2012).…”
Section: Preparation Of Microbial Inoculummentioning
confidence: 99%
“…MICs were determined by broth micro dilution (Tamokou et al, 2009;Fogue et al, 2012). Stock solutions of the tested samples were prepared in 10% v/v aqueous dimethylsulfoxide (DMSO) solution (Fisher chemicals, Strasbourg, France) at concentration of 2048 μg/mL.…”
Section: Determination Of the Minimum Inhibitory Concentrations (Micsmentioning
confidence: 99%